Choice Of Mechanomyography Sensors For Diverse Types Of Muscle Activities - Sundaraj, Kenneth; Talib, Irsa; Lam, Chee Kiang (Penerbit Universiti,UTeM, 2018)
Skeletal muscles contribute to the movement produced in the human body.They are therefore of vital importance for the study of muscles in various applications of movement including exercise,sports,prosthesis,rehabilitation,etc. The movement produced by skeletal muscles can be analyzed through various techniques like mechanomyography (MMG) and electromyography (EMG).MMG is a novel technique to assess skeletal muscle function through the oscillations produced during muscle contractions.MMG advocates well for its reliability,performance,and ease in application to other presently used techniques.MMG employs several types of sensors to observe vibrations in skeletal muscles.These sensors vary widely from application to type of movement and muscle.This review provides a comprehensive chunk of information on MMG sensor selection according to its placement,muscle function and condition,and limb movement and application. Recommendations for the choice of MMG sensor are given through extensive literature search over here.